Enhanced penetrative siRNA delivery by a nanodiamond drug delivery platform against hepatocellular carcinoma 3D models. Issue 38 (20th September 2021) - Xu, Jingru; Gu, Mengjie; Hooi, Lissa; Toh, Tan Boon; Thng, Dexter Kai Hao; Lim, Jhin Jieh; Chow, Edward Kai-Hua
Abstract : Comprehensive analysis of hepatocellular carcinoma 3D models revealed enhanced penetrative siRNA delivery by a nanodiamonds compared to liposomes. Nanodiamonds were able to improve siRNA's gene knockdown and anti-cancer effects in 3D tumor models. Abstract : Small interfering RNA (siRNA) can cause specific gene silencing and is considered promising for treating a variety of cancers, including hepatocellular carcinoma (HCC). However, siRNA has many undesirable physicochemical properties that limit its application. Additionally, conventional methods for delivering siRNA are limited in their ability to penetrate solid tumors. In this study, nanodiamonds (NDs) were evaluated as a nanoparticle drug delivery platform for improved siRNA delivery into tumor cells. Our results demonstrated that ND-siRNA complexes could effectively be formed through electrostatic interactions. The ND-siRNA complexes allowed for efficient cellular uptake and endosomal escape that protects siRNA from degradation. Moreover, ND delivery of siRNA was more effective at penetrating tumor spheroids compared to liposomal formulations. This enhanced penetration capacity makes NDs ideal vehicles to deliver siRNA against solid tumor masses as efficient gene knockdown and decreased tumor cell proliferation were observed in tumor spheroids. Evaluation of ND-siRNA complexes within the context of a 3D cancer disease model demonstrates the potential of NDs as a promising gene delivery platform against solid tumors, such as HCC.